Amniotic fluid and umbilical cord serum erythropoietin in term and prolonged pregnancies. (February 2019) - Seikku, Laura; Stefanovic, Vedran; Rahkonen, Petri; Teramo, Kari; Paavonen, Jorma; Tikkanen, Minna; Rahkonen, Leena
Abstract: Objective: Erythropoietin - a hormone regulating erythropoiesis - is a biomarker of chronic fetal hypoxia. High erythropoietin levels in fetal plasma and amniotic fluid are associated with increased risk of adverse neonatal outcome. Since the risk of perinatal morbidity and mortality is increased in pregnancies beyond 41 gestational weeks, we evaluated erythropoietin levels in amniotic fluid and umbilical cord serum in apparently low-risk term (≥ 37 gestational weeks) and prolonged pregnancies (≥ 41 gestational weeks) with labor induction. Study design: This prospective cohort study comprised 93 singleton pregnancies at 37 +0 -42 +1 gestational weeks, of which prolonged pregnancies numbered 63 (67.7%). Amniotic fluid samples were collected at time of labor induction by amniotomy. Umbilical cord blood samples for evaluation of pH, base excess, and umbilical cord serum erythropoietin were collected at birth. Erythropoietin levels were measured by immunochemiluminometric assay. Normal value of amniotic fluid erythropoietin level was defined as ≤ 3 IU/L, and abnormal value as ≥ 27 IU/L. Normal umbilical cord serum erythropoietin was defined as < 40 IU/L. Data on maternal pregnancy and delivery characteristics and short-term neonatal outcomes such as Apgar score were obtained from the hospital charts. Associations were calculated using Spearman's rank correlation coefficient. The Chi-square test, Fisher's exact test and the Mann-Whitney U test were utilized to determine differences in the study groups. Results: Amniotic fluid erythropoietin levels correlated with gestational age (r = 0.261, p = 0.012) and were higher among prolonged pregnancies as compared to term pregnancies (p = 0.005). There were 78 (83.9%) vaginal deliveries, and among these erythropoietin levels in amniotic fluid correlated with the levels in umbilical cord serum (r = 0.513, p < 0.000). Umbilical cord serum erythropoietin levels correlated with gestational age among vaginal deliveries (r = 0.250, p = 0.027). Erythropoietin levels in amniotic fluid and umbilical cord serum did not correlate with umbilical artery pH or base excess, or other adverse pregnancy outcome. Conclusions: In vaginal deliveries erythropoietin levels in amniotic fluid correlated with the levels in umbilical cord serum. Erythropoietin levels correlated with gestational age, probably due to weakening placental function and relative hypoxemia occurring in advanced gestation. However, in this relatively low-risk study population erythropoietin was not related to adverse delivery outcome.